If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + z)(5z + -1) = 0 Reorder the terms: (5 + z)(-1 + 5z) = 0 Multiply (5 + z) * (-1 + 5z) (5(-1 + 5z) + z(-1 + 5z)) = 0 ((-1 * 5 + 5z * 5) + z(-1 + 5z)) = 0 ((-5 + 25z) + z(-1 + 5z)) = 0 (-5 + 25z + (-1 * z + 5z * z)) = 0 (-5 + 25z + (-1z + 5z2)) = 0 Combine like terms: 25z + -1z = 24z (-5 + 24z + 5z2) = 0 Solving -5 + 24z + 5z2 = 0 Solving for variable 'z'. Factor a trinomial. (-5 + -1z)(1 + -5z) = 0Subproblem 1
Set the factor '(-5 + -1z)' equal to zero and attempt to solve: Simplifying -5 + -1z = 0 Solving -5 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1z = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1z = 0 + 5 -1z = 0 + 5 Combine like terms: 0 + 5 = 5 -1z = 5 Divide each side by '-1'. z = -5 Simplifying z = -5Subproblem 2
Set the factor '(1 + -5z)' equal to zero and attempt to solve: Simplifying 1 + -5z = 0 Solving 1 + -5z = 0 Move all terms containing z to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5z = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5z = 0 + -1 -5z = 0 + -1 Combine like terms: 0 + -1 = -1 -5z = -1 Divide each side by '-5'. z = 0.2 Simplifying z = 0.2Solution
z = {-5, 0.2}
| 42+12=30 | | 13a+14+6a= | | 2cos^2-cosx=1 | | 5x^2+12x+10=x^2+10x | | (2e^-4)-((5/7)e^-7)=x | | -7-8b=17 | | 3a^2-33ab+54b^2= | | 0.2(5-3)= | | 4u^2-20u=0 | | 9m-27=4m+1 | | (2e^-4)-((5/7)e^-7) | | 4/5p–4=2/3p | | 144=-16x | | 21-6a=-2b+-8 | | t+2+t+28+3t=180 | | 3m-9=4m+1 | | 3x+2x+7+4x-20=180 | | 2x-6(-2x-4)=94 | | y/x=3/8 | | (2c+5d)3=x | | -2y+9=3 | | (2c-5d)3=x | | 3(x+5)-12=9+3x-6 | | graphY-9=0 | | 9*320=16*a | | Y+1=3(x-3) | | B+12=42 | | 9*a=16*320 | | -5x+2(-x+9)=-31 | | K+15=0 | | 557.50+x=3482.50 | | c=346-856 |